224k views
1 vote
2(3x – 1) = –6x – 2 can someone help

User Nebs
by
5.1k points

1 Answer

4 votes

Let's solve your equation step-by-step.

2(3x−1)=−6x−2

Step 1: Simplify both sides of the equation.

2(3x−1)=−6x−2

(2)(3x)+(2)(−1)=−6x+−2(Distribute)

6x+−2=−6x+−2

6x−2=−6x−2

Step 2: Add 6x to both sides.

6x−2+6x=−6x−2+6x

12x−2=−2

Step 3: Add 2 to both sides.

12x−2+2=−2+2

12x=0

Step 4: Divide both sides by 12.

12x/12= 0/12

x=0

Answer:

x=0

HOPE THIS HELPS!!! :)

User Shingo
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.